KARAKTERISTIK COOKIES DARI TEPUNG SORGUM DAN TEPUNG ALMOND DENGAN PEMANIS STEVIA DAN GULA KELAPA KRISTAL - Budi Sustriawan; Nur Aini; Retno Setyawati; Rifka Hania; Revilla Tresna; Reza Irfan (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
The dependence of Indonesian people on consumption of wheat flour is high. In addition, wheat flour contains gluten, but not everyone can consume gluten. Indonesia has local food ingredients that can replace wheat flour, one of which is sorghum flour. Making cookies using sorghum flour and almond flour produces gluten-free cookies that are safe for people with gluten intolerants and lactose intolerants. In making cookies, a sweetener is needed, which can be used stevia sugar and crystal coconut sugar. The research aims to: 1) determine the effect of the proportion of sorghum flour and almond flour on the physical and chemical properties of cookies, 2) determine the effect of the proportion of stevia sugar and crystal coconut sugar on the physical and chemical properties of cookies, 3) determine the formulation of sorghum flour and almond flour with the addition of stevia sugar and crystal coconut sugar to produce cookies of the highest quality in terms of physical and chemical properties. The research used factorial randomized block design. The factors studied were the proportion of sorghum flour: almond flour consisted of 3 levels (1: 1; 2: 1; and 3: 1); and the proportion of stevia sugar: crystal coconut sugar consists of 3 levels (2: 1; 1: 1; 1: 2). The variables observed included ash content, moisture content, fat content, dissolved protein content, reducing sugar content and swelling volume. The best treatment is selected using the effectiveness index test. The results showed that the proportion of sorghum flour: almond flour affected the moisture content, ash content, fat content and dissolved protein content of cookies. Comparison of stevia sugar: crystal coconut sugar has an effect on water content, fat content, and reducing sugar content in cookies. The interaction between the two does not affect all variables. Based on chemical and physical variables, the selected treatment was a combination of T1K2 (sorghum 1 flour: almond flour 1 and stevia sugar 1: crystal coconut sugar 1). The physicochemical characteristics of cookies with sorghum flour and almond flour produced from the best treatment combination had a moisture content value of 4.45%, an ash content of 1.04%, a fat content of 33.57%, a dissolved protein content of 1.17%, a reducing sugar content of 5, 91%, and development volume of 60.48%